2001
DOI: 10.1093/nar/29.18.3742
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of restriction-modification systems as selfish mobile elements and their impact on genome evolution

Abstract: Restriction-modification (RM) systems are composed of genes that encode a restriction enzyme and a modification methylase. RM systems sometimes behave as discrete units of life, like viruses and transposons. RM complexes attack invading DNA that has not been properly modified and thus may serve as a tool of defense for bacterial cells. However, any threat to their maintenance, such as a challenge by a competing genetic element (an incompatible plasmid or an allelic homologous stretch of DNA, for example) can l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
475
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(494 citation statements)
references
References 114 publications
14
475
1
4
Order By: Relevance
“…Despite their function in cellular defense, these gene complexes tend to propagate as selfish elements to promote their own survival and increase their relative frequency (28,41,88). For example, the failure to segregate R-M-encoding plasmids equally during cell division results in cell death for the progeny lacking these plasmids (28,89).…”
Section: Additional Functions Of R-m Systems Selfish Genesmentioning
confidence: 99%
“…Despite their function in cellular defense, these gene complexes tend to propagate as selfish elements to promote their own survival and increase their relative frequency (28,41,88). For example, the failure to segregate R-M-encoding plasmids equally during cell division results in cell death for the progeny lacking these plasmids (28,89).…”
Section: Additional Functions Of R-m Systems Selfish Genesmentioning
confidence: 99%
“…In bacteria, methylation is best studied as part of restriction-modification (R-M) systems that have long been considered as contributing to bacterial immune response against incoming DNA including phages 4 . However, recent research has suggested that R-M systems may be 'selfish' elements that protect themselves against removal, through post-segregational killing of newly born progeny by pre-existing and stable restriction enzyme molecules [5][6][7][8][9][10][11] .…”
mentioning
confidence: 99%
“…A third type of postsegregational killing systems consists of several type II restriction-modification (RM) systems (29,31,48). A type II RM system is typically composed of a gene encoding a DNA endonuclease (restriction enzyme), which cleaves double-stranded DNA at a specific recognition sequence, and a gene encoding a DNA methyltransferase (modification enzyme), which methylates the same recognition sequence to protect DNA from the cleavage.…”
mentioning
confidence: 99%
“…Analyses of various prokaryotic genomes provide evidence that RM genes move between prokaryotic genomes (29,31). In fact, RM genes are often found on mobile genetic elements such as plasmids, viruses, transposons, and integrons (56).…”
mentioning
confidence: 99%
See 1 more Smart Citation